Emotional pictures and sounds: a review of multimodal interactions of emotion cues in multiple domains - Gerdes, Antje B. M.; Wieser, Matthias J.; Alpers, Georg W. (Frontiers in Psychology, 2014)
In everyday life, multiple sensory channels jointly trigger emotional experiences and one channel may alter processing in another channel. For example, seeing an emotional facial expression and hearing the voice’s emotional tone will jointly create the emotional experience. This example, where auditory and visual input is related to social communication, has gained considerable attention by researchers. However, interactions of visual and auditory emotional information are not limited to social communication but can extend to much broader contexts including human, animal, and environmental cues. In this article, we review current research on audiovisual emotion processing beyond face-voice stimuli to develop a broader perspective on multimodal interactions in emotion processing. We argue that current concepts of multimodality should be extended in considering an ecologically valid variety of stimuli in audiovisual emotion processing. Therefore, we provide an overview of studies in which emotional sounds and interactions with complex pictures of scenes were investigated. In addition to behavioral studies, we focus on neuroimaging, electro- and peripher-physiological findings. Furthermore, we integrate these findings and identify similarities or differences. We conclude with suggestions for future research.